2014
DOI: 10.1093/molehr/gau021
|View full text |Cite
|
Sign up to set email alerts
|

Getting too sweet: galectin-1 dysregulation in gestational diabetes mellitus

Abstract: Galectin-1 (gal-1) is a prototype carbohydrate-binding protein, whose dysregulation is associated with adverse pregnancy outcomes such as spontaneous abortion and pre-eclampsia. Furthermore, it is known that faulty gal-1 protein production or gene regulation can be caused by single-nucleotide polymorphisms in the LGALS1 gene. Gestational diabetes mellitus (GDM) is also an adverse pregnancy outcome and the most common metabolic disorder during gestation. However, gal-1 expression patterns during GDM remain larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…Its dysregulation has been associated with adverse pregnancy outcomes such as spontaneous abortion, preeclampsia, and HELLP syndrome. Blois et al recently studied placental tissues with dual immunofluorescence, demonstrating that serum galectin‐1 levels were reduced, while placental galectin‐1 was overexpressed in GDM women . In the present study, we confirmed an increase in galectin‐1 expression using LC‐MS E analysis of placental tissues from GDM women overcoming any problem due to the use of antibodies and their specificity (see Figure and Table ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Its dysregulation has been associated with adverse pregnancy outcomes such as spontaneous abortion, preeclampsia, and HELLP syndrome. Blois et al recently studied placental tissues with dual immunofluorescence, demonstrating that serum galectin‐1 levels were reduced, while placental galectin‐1 was overexpressed in GDM women . In the present study, we confirmed an increase in galectin‐1 expression using LC‐MS E analysis of placental tissues from GDM women overcoming any problem due to the use of antibodies and their specificity (see Figure and Table ).…”
Section: Resultssupporting
confidence: 84%
“…Blois et al recently studied placental tissues with dual immunofluorescence, demonstrating that serum galectin-1 levels were reduced, while placental galectin-1 was overexpressed in GDM women. 16 In the present study, we confirmed an increase in galectin-1 expression using LC-MS E analysis of placental tissues from GDM women overcoming any problem due to the use of antibodies and their specificity (see Figure 1 and Table 2). Its overexpression may counteract the placental inflammation typical of GDM, due to its role in controlling inflammatory response; in fact, it has been showed that galectin has a powerful immunoregulatory action due to its capacity to inhibit T-cell effector function by means of apoptotic and nonapoptotic mechanisms.…”
Section: Resultssupporting
confidence: 81%
“…However, because Gal-1 binds to a variety of glycoconjugates (11), further studies are warranted to elucidate whether other galectin-receptor interactions might take place under these circumstances. Finally, in contrast to healthy pregnant women, patients with gestational diabetes mellitus did not show any significant changes in Gal-1 levels during gestation (46). Of note, an immuneendocrine circuit regulated during the resolution of T1D and gestational diabetes mellitus may govern the broad immunosuppressive activities of Gal-1, leading to Th2 cytokine polarization (70,107) and Treg expansion (26,31,103).…”
Section: Gal-1 In Autoimmune Diseases: Resetting Tolerogenic Programsmentioning
confidence: 81%
“…Within the immune system, Gal-1 is synthesized and secreted by a wide range of cells, including activated T and B cells (22,23), macrophages (24), Foxp3 + regulatory T cells (Tregs) (25,26), tolerogenic dendritic cells (DCs) (27,28), gd T cells (29), microglia (30), and myeloid-derived suppressor cells (29). Remarkably, Gal-1 expression is prominent in immuneprivileged sites, such as placenta (31,32), testis (33,34), and the eye (35), and is significantly up-or downmodulated in inflammatory conditions, including microbial infection (36)(37)(38), autoimmunity (27,39), allergy (40,41), cancer (19,29,(42)(43)(44), reproductive disorders (31,32,45,46), neurodegenerative diseases (30), and myocardial infarction (47). Interestingly, in experimental models, Gal-1 expression peaks during the recovery phase of autoimmune disease (27,30), indicating a major role for this lectin during resolution of inflammation.…”
Section: Gal-1: a Sweet Checkpoint In The Resolution Of Inflammatory mentioning
confidence: 99%
“…Blois et al [44] previously showed a dysregulation of galectin-1 in GDM patients. While peripheral galectin-1 serum levels in GDM patients were lower compared to controls, expression in the placenta was significantly increased.…”
Section: Discussionmentioning
confidence: 93%